Germanistikstudium in Marokko – Probleme und Perspektiven - Bouchara, Abdelaziz (Stellenbosch Papers in Linguistics Plus, 2012)
In many African countries, German Studies has recently come under increasing pressure. In view of the globalization of economic and cultural processes, as well as the wider acceptance of French and English, German Studies finds itself in growing competition. This is also true in Morocco. In this context, as elsewhere, it has become essential to seek alternatives and to become innovative. Thus the traditional DaF (German as a foreign language) also has to redefine its roll. In this paper the author presents a professionally oriented course consisting of three modules: (1) business German, (2) German for tourism, and (3) intercultural communication. In addition, the general conditions under which such modules are to be introduced will be discussed. Keywords Schlüsselbegriffe: Germanistikstudium, Wirtschaftsdeutsch, Deutsch für den Tourismus, interkulturelle Kommunikation : German language and literature studies, German for business, German for tourism, intercultural communication